Development of dual-drug-loaded stealth nanocarriers for targeted and synergistic anti-lung cancer efficacy. (1st January 2018) - Chen, Juan; Yang, Xiaobing; Huang, Liuqing; Lai, Huixian; Gan, Chuanhai; Luo, Xuetao
Abstract: Combination chemotherapy is widely exploited for suppressing drug resistance and achieving synergistic anticancer efficacy in the clinic. In this paper, the nanostructured targeting methotrexate (MTX) plus pemetrexed (PMX) chitosan nanoparticles (CNPs) were developed by modifying methoxy polye (thylene glycol) (mPEG), in which PEGylation CNPs was used as stealth nanocarriers (PCNPs) and MTX was employed as a targeting ligand and chemotherapeutic agent as well. Studies were undertaken on human lung adenocarcinoma epithelial (A549) and Lewis lung carcinoma (LLC) cell lines, revealing the anti-tumor efficacy of nanoparticle drug delivery system. The co-delivery nanoparticles (MTX-PMX-PCNPs) had well-dispersed with sustained release behavior. Cell counting kit-8 (CCK8) has been used to measure A549 cell viability and the research showed that MTX-PMX-PCNPs were much more effective than free drugs when it came to the inhibition of growth and proliferation. Cell cycle assay by flow cytometry manifested that the MTX-PMX-PCNPs exhibited stronger intracellular taken up ability than free drugs at the same concentration. In vivo anticancer effect results indicated that MTX-PMX-PCNPs exhibited a significantly prolong blood circulation, more tumoral location accumulation, and resulted in a robust synergistic anticancer efficacy in lung cancer in mice. The results clearly demonstrated that such unique synergistic anticancer efficacy of co-delivery of MTX and PMX via stealth nanocarriers, providing a prospective strategy for lung cancer treatment.